Ultrasound-assisted encapsulation of Sacha Inchi (Plukenetia volubilis Linneo.) oil in alginate-chitosan nanoparticles - Elgegren, Mariela (2019)
Sacha inchi oil is rich in essential and non-essential fatty acids and other types of bioactive agents like tocopherols and polyphenolic compounds, which are very well-known antioxidants. In this study, the encapsulation of sacha inchi oil in alginate (AL) and chitosan (CS) nanoparticles was achieved with the assistance of high-intensity ultrasound. Nanoemulsion is the most effective delivery and high stability system for lipophilic bioactive agents. Chitosan and surfactant concentrations were varied to study their effect on particle formulations. Size, zeta-potential, polydispersity, and stability of particles were determined in time to optimize the preparation conditions. Sacha inchi oil encapsulated in AL-CS nanoparticles showed a higher loading efficiency and stability for short and long periods compared with other vegetable oils such as olive and soybean. Also, because of the types of tocopherols present in sacha inchi oil (γ- and δ-tocopherols), a much higher antioxidant activity (95% of radical reduction in 15 min) was found in comparison with nanocapsules with olive oil, which contain α-tocopherols. The particles showed high efficiency of protein loading at high concentration of bovine serum albumin (BSA) and a low rate of leaching profiles in various testing media like simulated gastric and intestinal fluids with/without enzymes, that is, pepsin 0.1% (w/v) and pancreatin 0.1% (w/v), respectively.